Case Report: Successful treatment of severe Guillain-Barré syndrome with paralytic ileus as a presenting symptom by intensive immunotherapy - Luo, Long; Chen, Lei; Li, Jun; Deng, Ye; Chen, Caihong; Cheng, Dan; Liu, Yang; Zhang, Huaping; Zhu, Ling (Frontiers in Immunology, 2025)
Involvement of the intestinal autonomic nerves in Guillain-Barré syndrome (GBS) can lead to paralytic ileus, a condition commonly observed in severe cases during later stages of the disease. Cases with paralytic ileus as a presenting symptom are very rare. We report a case of a 35-year-old male patient who was admitted to the hospital with acute abdominal pain persisting for 12 hours. Abdominal CT suggested small bowel obstruction, for which routine conventional pharmacological treatment were ineffective. Subsequently, the patient presented with multiple sets of cranial nerve paralysis, bilateral symmetrical delayed paralysis, distal limb numbness, respiratory failure, urinary retention, shock, and electrophysiology, suggesting axonal-type multifocal peripheral nerve damage. Notably, blood antiganglioside tests showed IgG positivity for anti-sulfatide antibodies, anti-GD1a antibodies, and anti-GT1a antibodies. The patient was administered plasma exchange combined with intravenous immunoglobulin, and symptoms gradually improved. The patient resumed independent ambulation within two months and returned to normal status at one year, with no recurrence of symptoms. Given that paralytic ileus can precede other neurological abnormalities in patients with GBS, early detection and individualized treatment are critical to reduce the risk of death and promote recovery. Here, we demonstrate that intensive immunotherapy is a viable therapeutic approach that can be clinically adopted for such conditions.